Silencing TNF-α in macrophages and dendritic cells for arthritis treatment. (August 2013) - Ye, C; Bhan, AK; Deshpande, V; Shankar, P; Manjunath, N
<x xml:space="preserve">Abstract</x> Objectives: Tumour necrosis factor (TNF)-α secreted by macrophages and dendritic cells (DCs) plays a predominant role in arthritis. Our previous studies suggest that a small peptide, RVG-9R (29-aa peptide derived from the rabies virus glycoprotein, fused to 9R residues), can deliver small interfering RNA (siRNA) to macrophages and DCs. We therefore tested whether knockdown of TNF-α expression in macrophages and DCs by RVG-9R/bound siRNA targeting TNF-α reduces the severity of collagen antibody-induced arthritis (CAIA) in mice. Method: Arthritis was induced in mice by injecting a combination of antibodies to collagen followed by lipopolysaccharide (LPS) treatment. Mice were also injected with TNF-α siRNA complexed with RVG-9R peptide or an irrelevant peptide RVMAT-9R on days 1, 3, 5, and 7. As a positive control, dexamethasone was injected intravenously. Paw thickness was measured every 2 days and the mice were killed on day 10 for testing synovial TNF-α levels and histological analysis of joints. Results: In control mice, arthritis developed on day 4 and reached its peak between day 7 and day 9. Treatment with siTNF-α bound to RVG-9R, but not to RVMAT-9R, resulted in reducing paw thickness scores to the same level as dexamethasone treatment, associated with reduced TNF-α level in synovial fluid. Histological analysis of joints in the control RVMAT-9R/TNF-α siRNA-treated mice showed marked pannus formation and destruction of cartilage and subchondrial bone, as well as severe infiltration of inflammatory cells into the synovium. By contrast, the joint pathology was markedly reduced in RVG-9R/TNF-α siRNA-treated mice resembling the dexamethasone-treated mice. Conclusions: Suppression of TNF-α expression in macrophages and DCs by RVG-9R-mediated siRNA delivery could potentially be a clinically viable strategy for treatment of arthritis.